A method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials.
Patent Information
- Application Number
- CN202510308138.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-03-17
AI Technical Summary
尽管该方法在中高温氧化退火过程中能以较低成膜损耗生成高密封性能的复相玻璃层,但单一的涂层结构在中低温区难以迅速形成高稳定性的熔融态富硅层,这导致涂层在中低温环境下难以有效修复结构缺陷,限制了其宽温域稳定防护时效
[0018]1.通过微波辅助方法快速实现了微晶覆载态粉体结构,既克服了传统制备过程中普遍存在的粉体受热差异导致微晶覆载不均匀的技术瓶颈,又利用了微波辅助加热快速高效制备的热动力学优势,大大缩短了制备周期,节约了能耗。
Smart Images

Figure CN120136439B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials, specifically a method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials. Background Technology
[0002] Carbon-based composite materials, due to their low density, high specific strength, low coefficient of thermal expansion, and excellent thermal shock resistance, have become promising lightweight and high-strength materials for thermal protection systems in aerospace vehicles. However, these materials are prone to rapid oxidation in oxidizing environments above 643K, leading to weight loss and structural damage, and the oxidation rate increases rapidly with increasing temperature. Anti-oxidation coating technology, by forming an oxygen-shielding layer on the surface of carbon materials, has been proven to effectively extend their service life.
[0003] In the field of antioxidant coatings, ZrB2 is considered one of the most promising candidate materials due to its high melting point, low relative density, and high thermal conductivity. However, when the temperature exceeds 1200℃, the main oxidation product B2O3 of ZrB2 coatings evaporates significantly, resulting in a porous and unprotected ZrO2 framework remaining in the coating. To improve this problem, transition metal silicides (such as MoSi2 and ZrSi2) are often used as film-forming modifiers. By forming a continuous silicon-rich layer in the ZrB2-based coating, the antioxidant properties of the coating can be significantly improved. However, the formation of the silicon-rich layer requires a high-temperature environment. At medium and low temperatures, the formation rate of the oxide film is slow, and its protective effect is weakened, making it difficult to effectively prevent oxygen penetration. Therefore, improving the film-forming ability and oxygen barrier properties of coatings at medium and low temperatures is of great significance.
[0004] Chen Yuexing et al. (Chen Yuexing. Study on oxygen barrier performance of binary transition metal silicide-modified ZrB2 coating based on self-propagating combustion synthesis [D]. China University of Mining and Technology, 2023) prepared a highly sintering-active binary transition metal silicide-modified ZrB2 composite powder using self-propagating combustion synthesis technology. This alloyed composite powder generated a Zr-B-Ta-Si-O multiphase glass layer with strong self-healing ability and low oxygen permeability during oxidation, significantly improving the coating's oxidation resistance in the inert oxidation stage. However, since the formation of the protective glass film requires a certain aging time, in the medium-low temperature protection range, it can only rely on the intrinsic physical structure of the coating to resist oxygen erosion, resulting in insignificant oxidation protection effect. Mao Chenhao et al. (Mao Chenhao. Structural oxygen barrier regulation and its anti-oxidation mechanism of ZrB2-SiC-MoSi2 coating prepared by reusing decommissioned MoSi2 [D]. China University of Mining and Technology, 2023) significantly enhanced the oxidation resistance of the coating through pre-oxidation self-damaging film formation treatment and doping with decommissioned MoSi2 modification. Although this method can generate a multiphase glass layer with high sealing performance with low film formation loss during medium- and high-temperature oxidation annealing, the single coating structure is difficult to form a highly stable molten silicon-rich layer quickly in the medium- and low-temperature region. This makes it difficult for the coating to effectively repair structural defects in the medium- and low-temperature environment, thus limiting its wide-temperature range stable protection time.
[0005] As is well known, high-quality powder is the foundation for preparing high-quality oxygen barrier coatings. There is an urgent need to develop high-quality powder preparation methods that can enable coatings to have protective effects at medium and low temperatures, so as to improve the wide temperature range protection capability of coatings. Summary of the Invention
[0006] The present invention aims to provide a method for preparing microcrystalline-coated ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, which utilizes in-situ microcrystalline coating modification to overcome the shortcomings of the existing technology.
[0007] To achieve the above objectives, the present invention employs the following technical solution:
[0008] A method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials specifically includes the following steps:
[0009] 1) Powder preparation and ball milling: ZrB2-MoSi2-ZrSi2 powder prepared by self-propagating synthesis was ball-milled and then loaded into a zirconia crucible.
[0010] 2) Crucible placement and microwave oven preparation: Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment.
[0011] 3) Microwave start-up and in-situ microcrystal coating: Start the microwave and simultaneously start the in-situ microcrystal coating process. After the process is completed, immediately remove the crucible and allow it to cool naturally.
[0012] 4) Product cooling and grinding: After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.
[0013] As a preferred embodiment, in step 1), the volume ratio of ZrB2, MoSi2, and ZrSi2 in the ZrB2-MoSi2-ZrSi2 powder is 9:1:1 to 9:5:1.
[0014] As a preferred embodiment, the microwave power in step 3) is 100W to 300W.
[0015] As a preferred embodiment, the in-situ microcrystalline coating treatment temperature in step 3) is 600–1000℃.
[0016] As a preferred embodiment, the in-situ microcrystal coating treatment time in step 1) is 2.5 to 5 minutes.
[0017] The advantages of this invention compared to the prior art are:
[0018] 1. Microcrystalline coated powder structures were rapidly realized using a microwave-assisted method, which not only overcame the technical bottleneck of uneven microcrystalline coating caused by differences in powder heating in traditional preparation processes, but also utilized the thermodynamic advantages of microwave-assisted heating for rapid and efficient preparation, greatly shortening the preparation cycle and saving energy.
[0019] 2. The microcrystalline supported powder prepared by this method exhibits a significant coating protection enhancement effect under medium and low temperature environments, and can rapidly form a dense oxygen barrier protective layer. Simultaneously, this method alleviates, to some extent, the formation of self-generated defects caused by in-situ grown microcrystalline support, further improving powder quality, strengthening the oxygen barrier effect of the coated powder structure at medium and low temperatures, and enhancing the long-term stable protection effect of the coating over a wide temperature range. Attached Figure Description
[0020] Figure 1 This is a process flow diagram of the present invention.
[0021] Figure 2 The X-ray diffraction phase analysis results of the powder obtained in Examples 1-5 and Comparative Example 1 of this invention are shown.
[0022] Figure 3 This is a scanning electron microscope (SEM) image of the microcrystalline-coated ZrB2-MoSi2-ZrSi2 powder obtained in Example 1 of this invention.
[0023] Figure 4This is a scanning electron microscope (SEM) image of the microcrystalline-coated ZrB2-MoSi2-ZrSi2 powder obtained in Example 2 of the present invention.
[0024] Figure 5 This is a scanning electron microscope (SEM) image of the microcrystalline-coated ZrB2-MoSi2-ZrSi2 powder obtained in Example 3 of the present invention.
[0025] Figure 6 This is a scanning electron microscope (SEM) image of the microcrystalline-coated ZrB2-MoSi2-ZrSi2 powder obtained in Example 4 of the present invention.
[0026] Figure 7 This is a scanning electron microscope (SEM) image of the microcrystalline-coated ZrB2-MoSi2-ZrSi2 powder obtained in Example 5 of the present invention.
[0027] Figure 8 This is the EDS energy spectrum of the microcrystalline supported ZrB2-MoSi2-ZrSi2 powder obtained in Example 1 of the present invention.
[0028] Figure 9 This is the EDS energy spectrum of the microcrystalline supported ZrB2-MoSi2-ZrSi2 powder obtained in Example 2 of the present invention.
[0029] Figure 10 This is the EDS energy spectrum of the microcrystalline coated ZrB2-MoSi2-ZrSi2 powder obtained in Example 3 of the present invention.
[0030] Figure 11 This is the EDS energy spectrum of the microcrystalline supported ZrB2-MoSi2-ZrSi2 powder obtained in Example 4 of the present invention.
[0031] Figure 12 This is the EDS energy spectrum of the microcrystalline supported ZrB2-MoSi2-ZrSi2 powder obtained in Example 5 of the present invention.
[0032] Figure 13 This is a scanning electron microscope (SEM) image of the ZrB2-MoSi2-ZrSi2 powder obtained in Comparative Example 1 of this invention.
[0033] Figure 14 The image shows the EDS energy spectrum of the ZrB2-MoSi2-ZrSi2 powder obtained in Comparative Example 1 of this invention. Detailed Implementation
[0034] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any reasonable combination of the specific embodiments.
[0035] Example 1:
[0036] This embodiment relates to a method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, specifically as follows:
[0037] (1) ZrB2-MoSi2-ZrSi2 powder (volume ratio 9:1:1) prepared by self-propagating synthesis was ball-milled and then loaded into a zirconium oxide crucible.
[0038] (2) Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment.
[0039] (3) Start the microwave (microwave power: 200W) and simultaneously start the in-situ microcrystal coating treatment program (treatment temperature: 600℃, treatment time: 3.5min). After the treatment is completed, immediately remove the crucible and allow it to cool naturally.
[0040] (4) After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.
[0041] The phase structure, microstructure, and EDS spectrum of the obtained powder are as follows: Figure 2 , Figure 3 and Figure 8 As shown in Table 1, to further verify the powder quality, the results of the ultra-high temperature static oxidation protection efficiency of the powder obtained in Example 1 after coating are shown in Table 1.
[0042] Example 2:
[0043] This embodiment relates to a method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, specifically as follows:
[0044] (1) ZrB2-MoSi2-ZrSi2 powder (volume ratio 9:2:1) prepared by self-propagating synthesis was ball-milled and then loaded into a zirconium oxide crucible.
[0045] (2) Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment.
[0046] (3) Start the microwave (microwave power: 100W) and simultaneously start the in-situ microcrystal coating treatment program (treatment temperature: 800℃, treatment time: 2.5min). After the treatment is completed, immediately remove the crucible and allow it to cool naturally.
[0047] (4) After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.
[0048] The phase structure, microstructure, and EDS spectrum of the obtained powder are as follows: Figure 2 , Figure 4 and Figure 9 As shown in Table 1, to further verify the powder quality, the results of the ultra-high temperature static oxidation protection efficiency of the powder obtained in Example 1 after coating are shown in Table 1.
[0049] Example 3:
[0050] This embodiment relates to a method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, specifically as follows:
[0051] (1) ZrB2-MoSi2-ZrSi2 powder (volume ratio 9:3:1) prepared by self-propagating synthesis was ball-milled and then loaded into a zirconium oxide crucible.
[0052] (2) Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment.
[0053] (3) Start the microwave (microwave power: 200W) and simultaneously start the in-situ microcrystal coating treatment program (treatment temperature: 800℃, treatment time: 3.5min). After the treatment is completed, immediately remove the crucible and allow it to cool naturally.
[0054] (4) After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.
[0055] The phase structure, microstructure, and EDS spectrum of the obtained powder are as follows: Figure 2 , Figure 5 and Figure 10 As shown in Table 1, to further verify the powder quality, the results of the ultra-high temperature static oxidation protection efficiency of the powder obtained in Example 1 after coating are shown in Table 1.
[0056] Example 4:
[0057] This embodiment relates to a method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, specifically as follows:
[0058] (1) ZrB2-MoSi2-ZrSi2 powder (volume ratio 9:4:1) prepared by self-propagating synthesis was ball-milled and then loaded into a zirconium oxide crucible.
[0059] (2) Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment.
[0060] (3) Start the microwave (microwave power: 300W) and simultaneously start the in-situ microcrystal coating treatment program (treatment temperature: 800℃, treatment time: 5min). After the treatment is completed, immediately remove the crucible and allow it to cool naturally.
[0061] (4) After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.
[0062] The phase structure, microstructure, and EDS spectrum of the obtained powder are as follows: Figure 2 , Figure 6 and Figure 11 As shown in Table 1, to further verify the powder quality, the results of the ultra-high temperature static oxidation protection efficiency of the powder obtained in Example 1 after coating are shown in Table 1.
[0063] Example 5:
[0064] This embodiment relates to a method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, specifically as follows:
[0065] (1) ZrB2-MoSi2-ZrSi2 powder (volume ratio 9:5:1) prepared by self-propagating synthesis was ball-milled and then loaded into a zirconium oxide crucible.
[0066] (2) Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment.
[0067] (3) Start the microwave (microwave power: 200W) and simultaneously start the in-situ microcrystal coating treatment program (treatment temperature: 1000℃, treatment time: 3.5min). After the treatment is completed, immediately remove the crucible and allow it to cool naturally.
[0068] (4) After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.
[0069] The phase structure, microstructure, and EDS spectrum of the obtained powder are as follows: Figure 2 , Figure 7 and Figure 12 As shown in Table 1, to further verify the powder quality, the results of the ultra-high temperature static oxidation protection efficiency of the powder obtained in Example 1 after coating are shown in Table 1.
[0070] Comparative Example 1:
[0071] This comparative example involves ZrB2-MoSi2-ZrSi2 powder, which is ZrB2-MoSi2-ZrSi2 powder without microcrystalline coating treatment, specifically: ZrB2-MoSi2-ZrSi2 powder (volume ratio 9:5:1) prepared by self-propagating synthesis method.
[0072] The phase structure, microstructure, and EDS spectrum of the obtained powder are as follows: Figure 2 , Figure 13 and Figure 14 As shown in Table 1, the results of the static oxidation protection efficiency of the powder obtained in Comparative Example 1 after coating at 1700℃ are shown to further verify the powder quality.
[0073] Based on Examples 1-5, steps (2) to (4) were omitted, i.e., no microcrystalline coating treatment was performed. The sample obtained in Comparative Example 1 was in a non-microcrystalline coated state. In this state, the oxygen barrier effect of the powder sample after coating was poor, and it was difficult to quickly form a highly stable molten silicon-rich layer in the medium and low temperature range. This resulted in the coated product being unable to effectively repair structural defects in the medium and low temperature environment, thus limiting the protection time. Therefore, the static oxidation protection efficiency of the powder obtained in Comparative Example 1 after coating at 1700℃ was significantly lower than that of Examples 1-5.
[0074] Table 1 shows the static oxidation protection efficiency of the obtained powder at 1700℃ after coating.
[0075] Example 1 99.63 Example 2 99.78 Example 3 99.85 Example 4 99.82 Example 5 99.74 Comparative Example 1 99.51
[0076] Table 1
[0077] This invention overcomes the technical bottleneck of uneven microcrystal coating caused by the difference in powder heating in the traditional preparation process. It also shortens the preparation cycle, saves energy, alleviates the generation of self-generated defects caused by in-situ grown microcrystal coating to a certain extent, further improves the powder quality, strengthens the oxygen barrier of the medium and low temperature structure after powder coating, and improves the stability and protection time of the coating over a wide temperature range.
[0078] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention; the actual structure is not limited thereto. In conclusion, if those skilled in the art are inspired by this description and design similar structures and embodiments without departing from the spirit of the invention, such designs should fall within the protection scope of the present invention.
Claims
1. A method for preparing microcrystalline supported ZrB2-MoSi2-ZrSi2 powder for oxygen barrier coating on carbon-based composite materials, characterized in that, Specifically, the following steps are included: 1) Powder preparation and ball milling: ZrB2-MoSi2-ZrSi2 powder was prepared by self-propagating synthesis with a volume ratio of ZrB2, MoSi2 and ZrSi2 of 9:1:
1. After being ball-milled, the powder was loaded into a zirconia crucible. 2) Crucible placement and microwave oven preparation: Place the zirconium oxide crucible containing ZrB2-MoSi2-ZrSi2 into a microwave-assisted high-temperature furnace for in-situ microcrystal loading treatment. 3) Microwave start-up and in-situ microcrystal coating: Start the microwave with a power of 200W, and simultaneously start the in-situ microcrystal coating process. The processing temperature is 600℃ and the processing time is 3.5min. After the processing is completed, immediately remove the crucible and allow it to cool naturally. 4) Product cooling and grinding: After cooling to room temperature, the product in the dry pot is taken out and ground evenly to obtain microcrystalline supported ZrB2-MoSi2-ZrSi2 powder.